Embryology of the Vascular System: Implications for Variants - Patel, Ronak K.; Simmons, Curtis L.; Ozen, Merve (Seminars in Interventional Radiology, 2025)
The vascular system is an intricate system that develops during early periods of embryogenesis. Through a complex signaling pathway of vasculogenesis and angiogenesis, embryonic vessels grow and coalesce, which allows nutrient and waste management. Dysfunction in these endothelial cells gives rise to vascular variants. Throughout gestational development, vascular variants can form in different organ systems such as the thoracic cavity, hepatic, renal, and lower pelvis. It is clinically very important for physicians to recognize these variants, as these variants can predispose to certain illnesses and treatment of patients surgically. This article discusses the embryology and vascular variants of the arterial system with a focus on the thoracic cavity, hepatic, renal, and pelvic variations to help aid in minimizing technical complications during procedures.
Keywords: embryology; variants; vascular; hepatic; renal